Traumatic triangular fibrocartilage complex tears: arthroscopic treatment in the athlete - Pogliacomi, F.; Armillotta, L.; Tocco, S.; Defilippo, M.; Corradi, M.; Ceccarelli F. (Medicina dello Sport, 2012)
Aim. Traumatic triangular fibrocartilage complex (TFCC) tears can be particularly disabling in the athlete. Treatment options of TFCC injuries vary along a wide spectrum based on acuteness and location of the tear as well as associated osseous and capsular-ligamentous lesions. The aim of this study was to evaluate the results of arthroscopic treatment of traumatic TFCC tears in high-level athletes. Methods. Between January 2006 and December 2010, 10 athletes with traumatic TFCC tear underwent wrist arthroscopy. The surgical technique (repair or debridement) was selected according to the location of the ruptures, which were divided using the Palmer classification. Pre-surgery and follow-up Modified Mayo Wrist Score (MMWS) and Patient Rated Wrist/Hand Evaluation (PRWHE) were recorded. Results. TFCC were repaired in 7 and debrided in 3 patients. MMW and PRWHE scores improved in all cases. Return to sport (RTS) averaged 3.5 months (range, 3-8) from surgery. In 1 patient there was an associated condition (positive ulnar variance and initial chondromalacia of the ulnar head) which delayed return to play to 8 months. Conclusion. Arthroscopic treatment of traumatic TFCC tears is the treatment of choice in high-level athletes who respond poorly to non-operative treatment regimens. RTS may be delayed in patients with associated ulnar sided wrist conditions.